【计算】(3分之1a²b)³×(-9ab³)÷(-2分之1a的5次方b³)【计算】(3分之1a²b)³×(-9ab³)÷(-2分之1a的5次方b³)(-x+2分之1)(x+2分之1)

【计算】(3分之1a²b)³×(-9ab³)÷(-2分之1a的5次方b³)【计算】(3分之1a²b)³×(-9ab³)÷(-2分之

【计算】(3分之1a²b)³×(-9ab³)÷(-2分之1a的5次方b³)【计算】(3分之1a²b)³×(-9ab³)÷(-2分之1a的5次方b³)(-x+2分之1)(x+2分之1)
【计算】(3分之1a²b)³×(-9ab³)÷(-2分之1a的5次方b³)
【计算】
(3分之1a²b)³×(-9ab³)÷(-2分之1a的5次方b³)
(-x+2分之1)(x+2分之1)

【计算】(3分之1a²b)³×(-9ab³)÷(-2分之1a的5次方b³)【计算】(3分之1a²b)³×(-9ab³)÷(-2分之1a的5次方b³)(-x+2分之1)(x+2分之1)
(3分之1a²b)³×(-9ab³)÷(-2分之1a的5次方b³)
=1/27a^6b^3×(-9ab^3)÷(-1/2a^5b^3)
=1/6×a^(6+1-5)b^(3+3-3)
=1/6a^2b^3
(-x+2分之1)(x+2分之1)
=1/4-x²